9514 1404 393
Answer:
(d) (-2, 6)
Explanation:
We can rewrite the function using vertex form.
f(x) = (x^2 +4x) +10
f(x) = (x^2 +4x +4) +10 -4 . . . . . . . add and subtract (4/2)^2
f(x) = (x +2)^2 +6
Compare to vertex form:
f(x) = (x -h)^2 +k
we see that (h, k) = (-2, 6) . . . . the vertex
_____
Additional comment
The value added and subtracted is the square of half the x-coefficient. Inside parentheses, that value "completes the square". Outside parentheses, that value ensures the overall function remains unchanged.